Pengaruh Lingkungan Masyarakat, Tingkat Pendidikan, dan Pendapatan Terhadap Minat Masyarakat Menjadi Tenaga Kerja Indonesia (TKI) Pada Desa Gunung Teguh Kecamatan Sangkapura - Lailatul Hijriyah; Tiara Khoerunnisa; Nanang Sutedja (Universitas Muhammadiyah Gresik, 2022)
Background - Gunung Teguh Village is one on Bawean Island which has been successful in maintaining population growth. The main source of livelihood for the people in Gunung Teguh Village is agriculture. The reduced level of employment opportunities in the country has generated interest and willingness of the people of a country to work in other countries. Therefore, some residents of Gunung Teguh Village migrate and work abroad to get a decent income. Objective - This study aims to test the effect of the community environment, education level, and income on people's interest in becoming Indonesian workers (TKI) in the study at Gunung Teguh Village, Sangkapura District. Design/Methodology/Approach - His research is a quantitative method, using the technique of Probability Sampling using Simple Random sampling. The analysis technique uses instrument testing, classical assumption testing, and hypothesis testing with test aids using the Statistical Package for the Social Sciences (SPSS). Finding - The results of this study indicate that the level of education has a significant effect on people's interest in becoming migrant workers and income has a significant effect on people's interest in becoming migrant workers. Simultaneously, it shows that the variable level of education and income have a simultaneous influence on people's interest in becoming migrant workers. With education possessed by prospective workers in the hope of getting a better job and bigger wages. Likewise, with income, prospective workers who are interested in working abroad are prospective workers who have low-income jobs. Research implications - This research contributes to the positive and significant influence of the community environment on people's interest in becoming Indonesian migrant workers (TKI). For Research limitations - This research was only conducted in the people of Gunung Teguh Village, Sangkapura District.